Cancer Prevention with Molecular Target Therapies 3.0 - Paleari, Laura (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Personalized medicine is playing an important role in cancer prevention. To date, it is clear that many cancers are molecularly distinct subtypes, and different therapeutic approaches would be required for each. This Special Issue brings together original research and review articles on molecular oncology with attention to the early detection and prevention of cancer. It highlights new findings, methods, and technical advances in molecular cancer research. The main feature of this reprint was to provide an open-source sharing of significant works in the field of molecular oncology that can increase our understanding of cancer development. Topics include:Molecular methods to personalize cancer screening and detection;Molecular target therapies to prevent cancer development and metastases;Identification and new aspects of cellular signaling molecules and pathways for target discovery, drug design and personalized and gender medicine;Drug repurposing for cancer prevention;Molecular modeling studies.